P205 HIV non-b subtypes in san francisco: migration but little local transmission. (14th July 2019) - O'Keefe, Kara; Pipkin, Sharon; Fatch, Robin; Scheer, Susan; Liegler, Teri; Mcfarland, Willi; Grant, Robert; Truong, Hong-Ha
Abstract : Background: Several HIV non-B subtypes and recombinants have been documented at low frequencies in the US. We characterized the viral diversity, epidemiology, and extent of local transmission and migration of non-B subtypes in San Francisco. Methods: Viral sequences from patients in care at local public and private health providers (2000–2016) were matched to the San Francisco Department of Public Health HIV/AIDS case registry. Phylogenies were reconstructed for the pol region of subtypes A1, C, D, G, CRF01_AE, CRF02_AG, and CRF07_BC sequences, with reference sequences from the LANL HIV database. Local transmission and global migration frequencies were compared based on phylogenetic topology. Epidemiologic associations between non-B subtypes and patient characteristics were assessed by multivariate logistic regression. Results: Of the 11, 382 viral sequences subtyped, 10, 669 were matched to 7, 236 registry cases. Fourteen non-B subtypes and CRFs were observed. Among registry cases, 141 (2%) had non-B subtypes or CRFs, and 72 (1%) had unnamed recombinant forms. The proportion of non-B subtypes increased over time. Of the 146 non-B transmission linkages identified, 104 (71%) appeared to represent migration from outside the study dataset, of which 86 (83%) had no close linkage to US reference strains. Twenty-six cases (18%) appeared to be local transmission, clustering with other sequences in this analysis. Of the 77 registry cases born outside of North America, 54 (70%) were phylogenetically linked to the case's region of birth. Cases with non-B subtypes or CRFs were associated with Asian/Pacific-Islander race/ethnicity (aOR=3.17; p<0.001), non-US birth country (aOR=11.02; p<0.001) and HIV diagnosis after 2009 (aOR=4.81; p<0.001). Conclusion: Non-B subtypes were present at low but increasing frequency in San Francisco. Local transmission of non-B subtypes appeared to be limited, as most non-B infections were likely acquired outside the US. Knowledge of subtype diversity can provide a better understanding of HIV global migration patterns, and inform treatment and prevention efforts. Disclosure: No significant relationships.